Pemeliharaan ayam kampung dan cara menghindari bau kandang pada ayam di Training Center Yayasan Kasih Untuk Bangsa (Yakub) Kejadian 1:28 - Marliana Lase; Ibelala Gea (International Forum of Researchers and Lecturers, 2024)
In writing this article, it discusses the maintenance of good broiler breeds of native chickens and avoiding odors sometimes in chicken manure. In the maintenance of native broiler chickens it is very important to pay attention to the schedule of giving food to chickens regularly. The purpose in writing the article is to explain that in the maintenance of broiler breeds of native chickens and avoiding manure in chickens at the Yayasan Kasih untuk Bangsa (YAKUB) training center. Using fermentation in feed mixed with EM 4 and given sawdust on the floor of the chicken coop. So that the cage in the chicken does not smell. The rearing of native chickens also applies a cage system where chickens cannot roam to avoid chicken mortality.